Selenium contamination in water; analytical and removal methods: a comprehensive review. Issue 15 (13th October 2022) - Ostovar, Mojtaba; Saberi, Nima; Ghiassi, Reza
ABSTRACT: Contamination of water resources has always been a threat to the human health as well as the environment. Selenium as a contaminant can enter water bodies through various anthropogenic causes such as mining and agricultural activities, fossil fuels combustion, as well as due to its application in industries such as glass, food, medical and etc. In this review paper, analytical techniques for measurement and identification of selenium in water have been reviewed. Also, different remediation methods for selenium removal from water have been investigated. Principally remediation methods are categorized in three groups: Physical, Biological and Chemical. Recent research advances in each group including Phytoremediation, Bioremediation, Electrocoagulation, Adsorption and etc. is discussed and their advantages and disadvantages are presented. Employing Nano materials in selenium removal from water is gaining a momentum due to higher removal efficiency, however, there is still research gap regarding synthetizing of long-lasting absorbents and improving removal efficiency of selenium species.